A centralized voltage regulation method for distribution networks containing high penetrations of photovoltaic power. (July 2021) - Ma, Wei; Wang, Wei; Chen, Zhe; Hu, Ruonan
Highlights: A new centralized voltage regulation method for a distribution network is proposed. The voltage fluctuation issues in a distribution network containing high levels of photovoltaic power are solved. The probability-based worst-case voltage scenarios of a distribution network are established. A fast decision-making algorithm is developed to select the best solution from the Pareto optimal set. Abstract: One of the most significant current concerns in distribution networks is the voltage fluctuations resulting from sharp changes of the active power of photovoltaic (PV) plants. Therefore, this paper proposes a novel worst-case voltage scenarios (WCVSs) based centralized voltage regulation method to suppress the voltage fluctuations of all buses in distribution networks, where the WCVSs are established according to probabilities of bus voltages exceeding the required voltage range. A mixed integer nonlinear programming (MINP) model is developed to coordinate on-load tap changers (OLTCs), capacitor banks (CBs), and PV plants, aiming at reducing switching operations of OLTCs and CBs, bus voltage variations, operating losses of distribution networks, and active power curtailments of PV plants. This paper employs the NSGA-II algorithm to find the Pareto optimal set of the established MINP model, and a fast decision-making algorithm is proposed to select the best solution from the Pareto optimal set. The proposed methods are conducted on a modified IEEE 33-bus distribution network with high penetrations of PV power. Simulation results show that the proposed voltage control methods can not only effectively deal with voltage fluctuation issues in the distribution network, but also reduce the operating costs of the distribution network.